Mössbauer Research of Surface-Surface Concentric-Zonal Color Effects in Zoloceramic Materials - A.K, Shokanov; M.F, Vereshchak; M.K, Kulbekov; I.A, Manakova; Sh.Zh, Hamraev; Y.A, Smikhan (International Journal of Geography and Geology, 2018)
The paper describes the results of a study of volume-surface concentric zonal color effects in gyro ceramic materials. The dependence of zonal flowers on the phase composition is established by the Mossbauer effects method.